Detection of financial and non-financial factors affecting the acceptance of going concern opinion - Ery Yanto, S.E., Ak., M.Ak.; Stasya Monifa (JAAF (Journal of Applied Accounting and Finance), 2022)
Financial statements are source of information for investors in determining which companies to invest in. Therefore, the reliability of financial statements has an important role. In order for financial reports to be reliable, there are two important things, namely reporting quality and earning quality factors. The auditor gives a fair opinion as a form of reporting quality. Thus, the going concern opinion is one of the opinions given by the auditor on earning quality. This study tries to examine what factors encourage the auditor to give going concern opinion to the company. The method used is a quantitative method using inferential statistics. In particular, the instrument used is logistic regression. The findings of this study are that companies that tend to get a going concern opinion have certain characteristics, among others, are large companies that have profits and have a fairly high level of debt. This finding can then be used by investors to identify companies that have the potential to get a going concern opinion.